Additive effect between IL-13 polymorphism and cesarean section delivery/prenatal antibiotics use on atopic dermatitis: a birth cohort study (COCOA). - So-Yeon Lee; Jinho Yu; Kang-Mo Ahn; Kyung Won Kim; Youn Ho Shin; Kyung-Shin Lee; Seo Ah Hong; Young-Ho Jung; Eun Lee; Song-I Yang; Ju-Hee Seo; Ji-Won Kwon; et al. (PLoS ONE, 2014)
BACKGROUND: Although cesarean delivery and prenatal exposure to antibiotics are likely to affect the gut microbiome in infancy, their effect on the development of atopic dermatitis (AD) in infancy is unclear. The influence of individual genotypes on these relationships is also unclear. To evaluate with a prospective birth cohort study whether cesarean section, prenatal exposure to antibiotics, and susceptible genotypes act additively to promote the development of AD in infancy. METHODS: The Cohort for Childhood of Asthma and Allergic Diseases (COCOA) was selected from the general Korean population. A pediatric allergist assessed 412 infants for the presence of AD at 1 year of age. Their cord blood DNA was subjected to interleukin (IL)-13 (rs20541) and cluster-of-differentiation (CD)14 (rs2569190) genotype analysis. RESULTS: The combination of cesarean delivery and prenatal exposure to antibiotics associated significantly and positively with AD (adjusted odds ratio, 5.70; 95% CI, 1.19-27.3). The association between cesarean delivery and AD was significantly modified by parental history of allergic diseases or risk-associated IL-13 (rs20541) and CD14 (rs2569190) genotypes. There was a trend of interaction between IL-13 (rs20541) and delivery mode with respect to the subsequent risk of AD. (P for interaction = 0.039) Infants who were exposed prenatally to antibiotics and were born by cesarean delivery had a lower total microbiota diversity in stool samples at 6 months of age than the control group. As the number of these risk factors increased, the AD risk rose (trend p<0.05). CONCLUSION: Cesarean delivery and prenatal antibiotic exposure may affect the gut microbiota, which may in turn influence the risk of AD in infants. These relationships may be shaped by the genetic predisposition.